Dorsal Augmentation in Rhinoplasty: A Survey and Review - Malone, Melanie; Pearlman, Steven (Facial Plastic Surgery, 2015)
Understanding the nuanced practices and grafting options of dorsal augmentation will improve outcomes and results in rhinoplasty. To better understand the practices of dorsal augmentation among our colleagues. To review the current literature regarding the indications, safety profiles, and outcomes of different materials used in dorsal augmentation. A PubMed search was performed to capture current articles containing reviews or large series regarding the safety and efficacy of various grafting materials used for dorsal augmentation. Of the many options available, autologous cartilage grafts maintain widespread use for dorsal augmentation and other techniques in rhinoplasty. Homologous cartilage grafts, namely irradiated rib, are a preferred alternative. Irradiated costal cartilage has been shown to have low complication rates and is unique in its abundance of supply, particularly in the revision rhinoplasty. Alloplastic implants, particularly silicone, are prevalent in Asian countries where they are a popular first-line choice. ePTFE has a favorable complication profile in primary rhinoplasty; however, caution is recommended when using ePTFE in revision cases. Porous polyethylene has a higher risk of associated complications than the other alloplastic implants listed, and therefore should be considered thoughtfully. Although cartilage is often the preferred graft for dorsal augmentation, there are many other autogenous, homologous, and alloplastic materials that have been shown to be safe and effective choices when applied in the proper setting.
Keywords: rhinoplasty; dorsal augmentation; revision rhinoplasty